An Information Support System for Identifying Farming System Part I : Development of A Computer Program Package - Lilik Sutiarso (agriTECH, 2002)
This study was undertaken to develop a computer program package for identifying a farming system that was focused in the water availability analysis, the optimizing of agricultural power and selected equipment and the senditivity analysis. The computer programs for all models were developed and written in FoxBASE command language. Three databases were obtained from the farm survey i.e.; climate, crop and power. All these databases can be appended, edited, deleted or displayed by the users through a menu of database mahagement system (DBMS). They were used to evaluate the utility of the computer programs as input data. The infromation system calculates the amoun of monthly water surplus and deficit, the optimum number of agricultural power (animal or power tiller) and its matching implement required and also change in the net return of crop production system due to the change of input variables such as crop price, yield, and production material cost. The system output for each analysis can be presented in three options by screen, printer and file that can be accessed to another language.